Promoting the well-being of elderly women through exercise. - Rowland, Linda (Cranfield University, 1997)
By the next decade, 5.1 percent of the British population will be over the age of eighty years. Women will make up over half of this figure. Finding ways of helping elderly women to maintain good health and therefore well-being, will become even more critical. Exercise is increasingly being recognised as a possible way of promoting health for elderly women, as evidence is emerging of the physical and psychological benefits that accrue from exercise. However, the empirical research evidence on exercise has derived mainly from young and middle-aged males, which means little is known about the specific benefits of exercise for the elderly and there are few tools to measure accurately exercise behaviour in this population. In the few exercise studies which have been conducted with the elderly, methodological flaws have often left the results unclear. Exercise up-take and adherence amongst elderly women is also low and psychological models have so far failed to adequately explain the reasons for this. To achievet he aim of this thesist o contributet o knowledgeo n the relationshipb etween physicala ctivity andw ell-beingi n elderlyw omen,t hree studiesa re conductedI.n study one,a postal questionnairefo r measuringe xerciseb ehaviour,b eliefsa nda ttitudesi n this population was first developed(, the London Health andF itnessQ uestionnaireL;I HFQ),w ith 248 elderly women. Secondi n studyt wo, a randomisedc ontrolledt rial of 100p ost-menopausawlo men assignedto eithera six monthb risk walking programmeo r homeopathicd oseo f exercisew as conducted.B aselinea nd six monthm easureso f staminal,e g strength,e xercisea ttitudes( using the LIHFQ) and subjectiveh ealths tatus( usingt he NottinghamH ealthP rofile;N HP) were taken.F inally, studyt hreei s exploratory,a nd examinesth e influenceso n elderlyw omen's participation in domestic and sporting physical activity, in a sample of 820 retirees from a major national retail company. The LHFQ and the NHP were used to obtain data. In study one,t he reliability andv alidity of the LHFQ proveda cceptableR. e-testr eliabilityw as bestf or numbero f hours spento n carryingo ut errandsa ndr ecreationael xerciseb, ut lowest for reports on past exercisee xperiencea nd identifyingb arrierst o exerciseT. he LIHEFQ appearsto haves atisfactoryfa ce,c ontenta nd constructv alidity. In study two, repeatedm easuresA NOVAs were usedt o detecta ny changesb etweena nd within the brisk walking and placeboe xerciseg roupso ver the six monthp eriod.M ean scores on the NBP indicatedt hat the brisk walking programmeh ada more beneficiailm pact on healths tatus,w ith significanti mprovemenitn perceivedp hysicaml obility. Significantp ositive changesw ere alson otedf or brisk walkerso n two exercisea ttitudes tatementsS. taminaa nd leg strengths ignificantlyi mprovedf or both groupso ver time. A numbero f threatst o the internalv alidity of the studyf indingse mergeda ndt hesea red iscusseda t length. In study three,m ultiple regressiona nalysesin dicatedt hat althoughd ifferentf actorsi nfluence domestica nd sportinga ctivity, good-healths tatusa nd age( beingy ounger)a re core variables influencingb oth thesea ctivities.I n addition,p ositivee xerciseb eliefsa nd attitudes,a nd past exercisee xperiencew ere shownt o influencee xerciseb ehaviour.